Sacrococcygeal teratoma - prognosis based on prenatal ultrasound diagnosis, single-center experience and literature review - Anna Jouzova; Martin Jouza; Jakub Turek; Romana Gerychova; Marta Jezova; Petr Janku; Lukas Hruban (BMC Pregnancy and Childbirth)
Abstract Introduction Sacrococcygeal teratoma (SCT) is the most common congenital tumor. The incidence of malignant types is rare but increases with late detection or in case of relapse. Prenatal diagnosis is based on ultrasound examination and magnetic resonance imaging (MRI). Since this is a rare congenital anomaly, we should report all cases to improve prenatal diagnosis and postnatal management. Material and methods Retrospective analysis of sixteen cases of sacrococcygeal teratoma delivered and treated at the University Hospital Brno between 2005 and 2020. The following criteria were evaluated: gestational week of the primary diagnosis, exact description of ultrasound findings, pregnancy management, delivery mode, correlation of prenatal ultrasound with postnatal findings in the newborn, as well as the occurrence of early and late complications in newborns and children. Results Out of sixteen cases, seven cases (43.8%) were indicated for pregnancy termination based on ultrasound findings, the parent’s decision, and an estimation of an adverse pregnancy outcome. In nine cases (56.2%), the pregnancy continued and was ended by delivery. In one case, there was an early postnatal death of a newborn after birth in the 25th week of gestation. In eight cases, live fetuses were born in which the tumor was surgically removed between day 1 and 14 months after birth. There was a strong correlation between the tumor description made by prenatal ultrasound diagnosis and related severe complications in newborns. The incidence of severe early and late complications in ongoing pregnancies was very low—only one case of infection in the surgical wound requiring reoperation (12.5%) was described. In two patients (25%), a transient stoma establishment was necessary for secondary ileus. One case of recurrence of the disease at two years of age occurred, requiring the administration of chemotherapy (12.5%), and one patient has mild persistent urinary incontinence. Conclusion Sacrococcygeal teratoma is one of the rarest congenital malformations. A detailed prenatal ultrasound examination is essential to estimate the pregnancy prognosis. The most predictive ultrasound predictor of favorable early and late postnatal outcomes and long-term child development is the presence of cystic sacrococcygeal formation, the most common tumor type, and the absence of signs of cardiac failure due to fetal anemia. In these cases, with early surgical treatment provided, the incidence of severe complications and long-term consequences in children is very low, and parents should be informed during prenatal counseling. It is necessary to register all the SCT cases due to the rarity of this congenital anomaly for further statistical analysis of the importance of ultrasound markers.